A revision of the Axylus group of Agraeciini (Orthoptera: Tettigoniidae: Conocephalinae) and of some other species formerly included in Nicsara or Anthracites Revision of the Indo-Australian Conocephalinae, part 3 - Ingrisch, Sigfrid (Zootaxa, 2015)
Axylus group is used to include the five genera Axylus Stål, 1877, Anthracites Redtenbacher, 1891 sensu stricto, Eucoptaspis Willemse, 1966, Eulobaspis gen. nov., and Heminicsara Karny, 1912. It is mainly based on a combination of the characters shape of pronotum, spiniform meso- and metasternal lobes, and similar basic ground plans of the male cerci, titillators and female subgenital plates. The five genera together with two superficially similar genera Euanthracites gen. nov. and Sulasara gen. nov. are fully revised. Papuacites gen. nov. is proposed for two New Guinean species formerly included in Anthracites. Nicsara Walker, 1869 is restricted to Australian species; Spinisternum Willemse, 1942 is synonymised with Heminicsara Karny, 1912; Odontocoryphus Karny, 1907 based on two nymphs is synonymised with Macroxiphus Pictet, 1888; Pseudoliara Karny, 1907 described after one nymph is regarded incertae sedis.       40 new combination of species are proposed: Axylus bimaculatus (Redtenbacher, 1891) comb. nov., A. inferior (Brunner, 1898) comb. nov., A. inflatus (Brunner, 1898) comb. nov., A. loboensis (De Haan, 1842) comb. nov., A. minutus (Dohrn, 1905) comb. nov., A. nigrifrons (Brunner, 1898) comb. nov., A. philippinus (Hebard, 1922) comb. nov., A, taylori (Hebard, 1922) comb. nov., and A. thoracicus (Dohrn, 1905) comb. nov. (all from Nicsara); Euanthracites apoensis (Hebard, 1922) comb. nov., E. femoralis (Dohrn, 1905) comb. nov., E. rufus (Ingrisch, 1998) comb. nov., and E. tibialis (Karny, 1931) comb. nov. (from Anthracites); Eucoptaspis inexpectatus (Willemse, 1953) comb. nov. (from Gonatacanthus Karny, 1907); Eulobaspis dehaani (Karny, 1920) comb. nov., E. emarginata (Karny, 1926) comb. nov., E. moluccana (Redtenbacher, 1891) comb. nov., E. personata (Karny, 1926) comb. nov., E. quadrimaculata (Karny, 1926) comb. nov., E. rotundata (Karny, 1926) comb. nov., and E. strigatipes (Bolivar, 1898) comb. nov. (from Nicsara); Eulobaspis lobaspoides (Karny, 1907) comb. nov. and E. ornata (Brunner, 1898) comb. nov. (from Axylus); Heminicsara excisa (Karny, 1926) comb. nov., H. insulana (Willemse, 1966) comb. nov., H. schlaginhaufeni (Karny, 1912) comb. nov., and H. viridipes (Karny, 1912) comb. nov. (from Nicsara); Heminicsara castaneipictus (Willemse, 1966) comb. nov., H. insularis (Willemse, 1942) comb. nov., and H. palauensis (Vickery & Kevan, 1999) comb. nov. (from Spinisternum); Heminicsara decipiens (Karny, 1926) comb. nov. and H. griffinii (Karny, 1911) comb. nov. (from Gonatacanthus); Heminicsara novaeguineae (Willemse, 1966) comb. nov. (from Eucoptaspis); Sulasara aethiops (Karny, 1931) comb. nov., S. karnyi (Willemse, 1932) comb. nov., and Sulasara sarasini (Karny, 1931) comb. nov. (from Nicsara); Papuacites nigrifrons (Karny, 1912) comb. nov. and P. nakanaiensis (Naskrecki & Rentz, 2010) comb. nov. (from Anthracites); Paramacroxiphus multispinosa (Bolivar, 1898) comb. nov. (from Nicsara); Palaeoagraecia globiceratus Vickery & Kevan, 1999 comb. nov. (from Macroxiphus). Odontocoryphus pullus Karny, 1907 becomes a new synonym of Macroxiphus sumatranus sumatranus (Haan, 1842).        87 species are described as new: nine species in Axylus: A. brachypterus sp. nov., A. dulang sp. nov., A. furcatus sp. nov., A. mengkoka sp. nov., A. montanus sp. nov., A. negros sp. nov. , A. superior sp. nov., A. totop sp. nov. , A. unicolor sp. nov.; six species in Anthracites: A. bilineatus sp. nov., A. flagellatus sp. nov., A. pyramidalis sp. nov., A. romblon sp. nov., A. sinuatus sp. nov., A. unispinus sp. nov.; four species in Euanthracites: E. bispinus sp. nov., E. eboreus sp. nov., E. ile sp. nov., E. uru sp. nov.; six species in Eucoptaspis: E. adonara sp. nov., E. hexamaculatus sp. nov., E. remotus sp. nov., E. stylatus sp. nov., E. trapezoides sp. nov., E. wawo sp. nov.; eight species in Eulobaspis: E. bacan C.Willemse & Ingrisch sp. nov., E. baduri sp. nov., E. buruensis sp. nov., E. ceramica C.Willemse & Ingrisch sp. nov., E. morotai sp. nov., E. sudirman sp. nov., E. ternate sp. nov., E. variata sp. nov.; 51 species in Heminicsara: H. albatros sp. nov., H. albipuncta sp. nov., H. albogeniculata Naskrecki & Ingrisch sp. nov., H. alticola sp. nov., H. ammea sp. nov., H. anggi sp. nov., H. bilobata sp. nov., H. cingima sp. nov., H. comprima sp. nov., H. coriformis sp. nov., H. corneli sp. nov., H. cyclops sp. nov., H. despecta Naskrecki & Ingrisch sp. nov., H. dilatata sp. nov., H. dividata sp. nov., H. dobo sp. nov., H. elongata Naskrecki & Ingrisch sp. nov., H. furcata sp. nov., H. gibba sp. nov., H. gugusu Naskrecki & Ingrisch sp. nov., H. illugi sp. nov., H. jacobii Karny, 1912, H. jayawijaya sp. nov., H. kelila sp. nov., H. kolombangara sp. nov., H. lamas Naskrecki & Ingrisch sp. nov., H. longiloba sp. nov., H. lord sp. nov., H. malu sp. nov., H. mamberamo sp. nov., H. manus sp. nov., H. montana sp. nov., H. nigra sp. nov., H. nomoensis sp. nov., H. obiensis sp. nov., H. ohu sp. nov., H. pak sp. nov., H. parallela Naskrecki & Ingrisch sp. nov., H. pinniger sp. nov., H. popoman sp. nov., H. rugosa sp. nov., H. scutula sp. nov., H. sica sp. nov., H. sinewit sp. nov., H. siwi sp. nov., H. stylata sp. nov., H. tabtab sp. nov., H. truncata Naskrecki & Ingrisch sp. nov., H. tumulus sp. nov., H. umasani sp. nov., H. wanuma sp. nov., H. zugi sp. nov.; and three species in Sulasara: S. armata sp. nov., S. renschi sp. nov., S. tambu sp. nov.